ANALYSIS OF THE IMPACT OF ANTHROPOGENIC ACTIVITIES ON GROUNDWATER QUALITY IN GREATER JOS URBAN AREA, PLATEAU STATE, NIGERIA - BEKA, CHRISTOPHER NENPOMIGYI; EZIASHI, AUGUSTINE CHUKWUMA; ALI, ANDESIKUTEB YAKUBU (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
The Greater Jos Urban Area has witnessed increase in human activities coupled with the shallow aquifers of a well mineralized geology. These have created a vulnerability situation that is deteriorating the quality of groundwater in Jos urban area. This groundwater quality is not envisaged along with the pace of rapid urban development and groundwater quality governance is either weak or not existing in the metropolis. The aim of this study is to examine the human influence and factors responsible for the variation of groundwater quality. This was carried out to develop ways of ensuring the sustainability of groundwater quality in the area.106 well water levels were measured to determine human influence and 72 samples tested for various parameters including pH, total dissolved solids (TDS), K, HCO3, Fe, Na, Ca, Mg, Cl, NO3, SO4, Cd, Pb, F, feacal coliforms and hardness following the United States Environmental Protection Agency (USEPA) standard procedures. The findings of the study indicated that Nitrates, feacal coliform, lead and cadmium had high values around the city center of Bukuru and Jos in the study area of the metropolis exceeding the SON (2015) standard for drinking water at certain points within the area. The factor analysis results indicated that the geology is controlling the quality of the groundwater and that human activities measured closely after the geology in ratio of one (1) part to four (4) respectively. The implication of this is that human activities chiefly due to poor sanitation, lack of development planning with cognizance to groundwater resources and weak groundwater quality governance were influencing the quality of the groundwater in the area. The study concluded that a framework for the Greater Jos Urban area to address urban groundwater quality governance should be developed along with proper land use planning to curb this menace. This would conceptualize how development can be planned alongside with the groundwater quality in the metropolis to achieve the sustainable management of groundwater resources in the study area.